Analisis Penerimaan Layanan Web Tracking dengan Penerapan Technology Acceptance Model (TAM) - Dien Novita; Della Oktaviany (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
Developments of technology allow businesses in Indonesia to develop its business activities to maintain good relations with customers. Most of the business activities already involve technology, both in terms of the use of hardware and software. In providing freight services, PT XYZ provides additional services to its customers, by giving Web Tracking feature. This feature is the media to check the position of shipments that have been submitted through PT XYZ. Then it needs to be analyzed receipt Tracking Web services. With descriptive analysis method with a sample of 235 respondents, analysis of acceptance of Web services Tracking for delivery of goods in PT XYZ quite well, seen from a variable in the Technology Acceptance Model (TAM) gained an average user agrees with Web services Tracking with percentages ranging between 65,87% to 98.81%. The high attitude to use technology from the users of 98.81% the results of this study, PT XYZ should improve usability and ease of use of Web Tracking service.